Prevalence, bacterial agents, and risk factors associated with subclinical mastitis in cattle from the Montevideo hamlet, Chaglla, Huánuco - Turpo Calcina, Jorge Suplicio (2024)
Bovine subclinical mastitis is one of the leading causes of economic losses in the dairy sector due to its impact on milk quality, the increase in somatic cell count, and the reduction of productive performance. The objective of this study was to gather information on the presence and distribution of this disease, identify the bacterial agents involved, and examine the factors contributing to risk in small herds in the Montevideo hamlet of the Chaglla district, Pachitea province, Huánuco region, Peru. A total of 187 lactating cows were evaluated using the California Mastitis Test and direct microscopic count. Positive samples were processed on selective and differential media for bacterial isolation, following phenotypic and biochemical identification protocols. Statistical analysis included prevalence estimation with 95% confidence intervals and logistic regression to identify vulnerability indicators. The prevalence of subclinical mastitis was 57.2% at the cow level and 35.8% at the udder quarter level. Higher frequency was observed in Holstein cows (70.9%) compared with crossbred and Brown Swiss cows. The most frequent bacterial agent detected was Staphylococcus aureus, followed by Enterobacter agglomerans and Escherichia coli. Multivariate regression showed a significant association between subclinical mastitis and the variables Holstein breed, higher parity number, and lower production level. No statistical relationship was found with hygienic management practices such as teat washing or drying. The results demonstrate a high sanitary burden due to subclinical mastitis in the extensive production system of Chaglla, underscoring the need for preventive interventions tailored to the local context.